The story of the Arizona Diamondbacks - Gilbert, Sara. (Mankato, MN : Creative Education, 2012)
"The history of the Arizona Diamondbacks professional baseball team from its inaugural 1998 season to today, spotlighting the team's greatest players and most memorable moments"--Provided by publisher.
Includes index.
Keywords: Arizona Diamondbacks (Baseball team) -- History -- Juvenile literature; Arizona Diamondbacks (Baseball team) -- History